K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 7 2021

\(\sqrt{27}-\sqrt{35}>\sqrt{25}-\sqrt{36}=5-6=-1\)

\(6-\sqrt{51}< 6-\sqrt{49}=6-7=-1\)

=> \(\sqrt{27}-\sqrt{35}>6-\sqrt{51}\)

17 tháng 12 2018

\(\sqrt{27}-\sqrt{12}-\sqrt{2016}>\)-44

b: \(\sqrt{2017}-\sqrt{2016}=\dfrac{1}{\sqrt{2016}+\sqrt{2017}}\)

\(\sqrt{2016}-\sqrt{2015}=\dfrac{1}{\sqrt{2016}+\sqrt{2015}}\)

mà \(\sqrt{2016}+\sqrt{2017}< \sqrt{2016}+\sqrt{2015}\)

nên \(\sqrt{2017}-\sqrt{2016}>\sqrt{2016}-\sqrt{2015}\)

\(\sqrt{2017}-\sqrt{2016}=\dfrac{1}{\sqrt{2017}+\sqrt{2016}}\)

\(\sqrt{2016}-\sqrt{2015}=\dfrac{1}{\sqrt{2016}+\sqrt{2015}}\)

2017>2015

=>căn 2017>căn 2015

=>\(\sqrt{2017}+\sqrt{2016}>\sqrt{2016}+\sqrt{2015}\)

=>\(\dfrac{1}{\sqrt{2017}+\sqrt{2016}}< \dfrac{1}{\sqrt{2016}+\sqrt{2015}}\)

=>\(\sqrt{2017}-\sqrt{2016}< \sqrt{2016}-\sqrt{2015}\)

19 tháng 7 2019

\(\sqrt{27}-\sqrt{12}-\sqrt{2016}>\sqrt{25}-\sqrt{16}-\sqrt{2025}\)

\(=5-4-45=-44\)

Vậy \(\sqrt{27}-\sqrt{12}-\sqrt{2016}>-44\)

19 tháng 7 2019

Có : \(\sqrt{12}< \sqrt{16}=4\)

         \(\sqrt{2016}< \sqrt{2025}\)         => \(\sqrt{12}+\sqrt{2016}< 4+45\)

                                                                 => \(-\sqrt{12}-\sqrt{2016}>-49\)(1)

Lại có : \(\sqrt{27}>\sqrt{25}=5\)(2)

Từ (1),(2) có : \(\sqrt{27}-\sqrt{12}-\sqrt{2016}>5-49\)or \(\sqrt{27}-\sqrt{12}-\sqrt{2016}>-44\)

Ta có: \(12>9\)

\(6\sqrt{3}>4\sqrt{5}\)

Do đó: \(12+6\sqrt{3}>9+4\sqrt{5}\)

\(\Leftrightarrow\sqrt{12+6\sqrt{3}}>\sqrt{9+4\sqrt{5}}\)

5 tháng 12 2021

Ta có: √12+6√3 = √9+6√3+√3

=3+√3 (1)ta co√9+4√5=√5+2 (2)từ (1) và (2) ta co√12+6√3>√9+4√5 
7 tháng 7 2016

\(\sqrt{35}+\sqrt{99}< \sqrt{36}+\sqrt{100}=6+10=16\)

Vậy \(\sqrt{35}+\sqrt{99}< 16\)

HQ
Hà Quang Minh
Giáo viên
23 tháng 8 2023

\(a,\sqrt{42}=\sqrt{3\cdot14}>\sqrt{3\cdot12}=6\\ \sqrt[3]{51}=\sqrt[3]{17}< \sqrt[3]{3\cdot72}=6\\ \Rightarrow\sqrt{42}>\sqrt[3]{51}\\ b,16^{\sqrt{3}}=4^{2\sqrt{3}}\\ 18>12\Rightarrow3\sqrt{2}>2\sqrt{3}\Rightarrow4^{3\sqrt{2}}>4^{2\sqrt{3}}\\ \Rightarrow4^{3\sqrt{2}}>16^{\sqrt{3}}\)

\(c,\left(\sqrt{16}\right)^6=16^3=4^6=4^2\cdot4^4=4^2\cdot16^2\\ \left(\sqrt[3]{60}\right)^6=60^2=4^2\cdot15^2\\ 4^2\cdot16^2>4^2\cdot15^2\Rightarrow\sqrt{16}>\sqrt[3]{60}\Rightarrow0,2^{\sqrt{16}}< 0,2^{\sqrt[3]{60}}\)

30 tháng 6 2021

Ta có \(\sqrt{8}+3< \sqrt{9}+3=3+3=6\)

=> \(\sqrt{8}+3< 6\)

Ta có \(\sqrt{48}< \sqrt{49};\sqrt{35}< \sqrt{36}\)

=> \(\sqrt{48}+\sqrt{35}< \sqrt{49}+\sqrt{46}\)

=> \(\sqrt{48}+\sqrt{35}< 13\)

=> \(\sqrt{48}< 13-\sqrt{35}\)

c) Ta có \(-\sqrt{19}< -\sqrt{17}\)

=> \(\sqrt{31}-\sqrt{19}< \sqrt{31}-\sqrt{17}\)

=> \(\sqrt{31}-\sqrt{19}< \sqrt{36}-17=6-\sqrt{17}\)

d) Ta có \(9=\sqrt{81}\Leftrightarrow\sqrt{81}>\sqrt{80}\);

\(-\sqrt{58}>-\sqrt{59}\)

=> \(\sqrt{81}-\sqrt{58}>\sqrt{80}-\sqrt{59}\)

<=> \(9-\sqrt{58}>\sqrt{80}-\sqrt{59}\)